Eliciting expert opinion via Delphi survey / Norazian Mohamad Yusuwan … [et al.] - Mohamad Yusuwan, Norazian; Adnan, Hamimah; Hashim, Norfashiha; Baharuddin, Har Einur Azrin (Research Innovation Business Unit, 2014)
The Delphi technique has been recognised to be amongst the most powerful techniques of eliciting expert opinion. This technique has been named after the ancient Greek temple where the oracle could be found (Grisham, 2009). It was originally developed by Olaf Helmer and his colleagues at the RAND Corporation in the early 1950s, and has been designed intentionally to remove conference room impediment to a true expert consensus (Gordon, 1994; Yousuf, 2007). For over half a century of its existence the Delphi technique has gained popularity and has been employed in a various field of studies such as in health care (Cramer, Klasser, Epstein, & Sheps, 2008; Sharkey & Sharples, 2001), business (Czinkota & Ronkainen, 2005; McGuire & Cseh, 2006), education (Kurubacak, 2007; Rice, 2009), management (Loo, 2002; Schwarz, 2008) as well as in engineering and construction (Brewer & Gajendran, 2009; Xia, Chan, & Zuo, 2012). This method has been designed as a group communication process aims to achieve a convergence of opinion on a specific real-world issue from respondents within their domain of expertise (Hsu & Sandford, 2007). As defined by Linstone and Turoff (1975), the Delphi method “may be characterised as a method for structuring a group communication process so that the process is effective in allowing a group of individuals, as a whole, to deal with a complex problem”. The rationale for the procedure as pointed out by Dalkey (1969), is that “two heads are better than one”. This paper attempt to provide an overview on the Delphi technique and how it has been implemented in an on-going PhD research which aimed to validate findings obtained from earlier questionnaire survey and semi-structured interview with regards to the current practice in of construction industry practitioners in substantiating and assessing Extension of Time (EoT application in Malaysian construction industry. This paper will not reveal the overall outcome of the research, but only results from the Section B of the questionnaire will be discussed. The discussion in this paper will cover the features and characteristics of the Delphi technique, and the implementation of this technique in the proposed research. This paper is expected to provide a clear picture on the Delphi technique that might be useful to the other researcher to be taken into their consideration in selecting the best-suited method of data collection for their research. findings from the questionnaire is expected to produce a statistical report with a high degree of confidence, while the qualitative approach on the other hand is expected to provide a rich data that could facilitate detailed explanation on the subject being studied as it based on respondent’s perspectives of their work experience, which will reflect the real situation of construction industry. In order to achieve a robust and highly credible research finding, a quantitative data analysis using statistical software will be conducted to obtain consensus from the experts on the subject being studied i.e. extension of time application, which will be collected via a Delphi survey. At the end of this research, an appropriate framework for a successful EoT application will be developed based on the findings from the triangulation approach. Results obtained through the Delphi technique will provide a sound basis for framework development process.